Revitalisasi Pancasila dalam Penegakan Hukum yang Berkeadilan di Indonesia - Farida Sekti Pahlevi (Justicia Islamica, 2016)
Pancasila has become an agreement of the Indonesian people as the state foundation of the Unitary State of the Republic of Indonesia, but in its implementation efforts experienced various obstacles both internal and external. Pancasila as the nation's worldview needs to be implemented in real life, this has been exemplified by the founding fathers through hard work and struggle resulting in Indonesia's independence. Concern about the condition of the law that is in favor so far from the element of justice makes the mind interested in discussing whether the values taught by Pancasila are still heeded or ignored. Pancasila, which is the ideology of the nation as a way of life and a foundation in the activities of society, nation and state, seems to be only used as memorization without application, including in the legal field. The quality of the state which is the benchmark for safeguarding the nation's ideology is highly anticipated to control the implementation of a just law based on the noble values of Pancasila. Thus it will realize the situation and conditions that are coveted and expected by all Indonesian people in all aspects, especially legal aspects. Pancasila as the basis of the State then serves as a source of law that applies in Indonesia. All laws and regulations must be an elaboration of the principles contained in Pancasila. All laws and regulations that are not in accordance with Pancasila are null and void. Therefore, to be able to understand the accuracy of a legislation, it is necessary to understand the concepts, principles and values contained in Pancasila. Pancasila as the basis of the state is implemented into legal norms that are compelling, binding and contain sanctions. Anyone who does not implement or comply with it will be dealt with in accordance with applicable law. Therefore, it is necessary to organize law enforcement against all laws which are the elaboration of the Pancasila State foundation.